Prediksi Inflasi Sumatera Utara dengan Maximal Overlap Discrete Wavelet Transfrom - Khaila Afsari; Machrani Adi Putri Siregar; Rima Aprilia (Unversitas Muhammadiyah Mataram, 2024)
Abstract: The aim of this research is to determine the mathematical model and level of accuracy in predicting the inflation rate in North Sumatra for 2022 using the Maximal Overlap Discrete Wavelet Transform and to find out the results of predicting the inflation rate in North Sumatra for 2023-2025. This North Sumatra inflation prediction research applies the Maximal Overlap Discrete Wavelet Transform method using Haar wavelets in its solution. The results obtained are a prediction model for the inflation rate of North Sumatra, namely 0.997147X+25.807 with an interpretation value from the MAPE accuracy results of 15%. This shows that if the accuracy value is 10-20%, it is said to be good to use so that the Maximal Overlap Discreate Wavelet Transform method can be used. to predict the inflation rate. The prediction results obtained are that North Sumatra will experience the largest inflation in 2023 in January with a Month to Month inflation rate of 24.37% and the smallest inflation in 2023 in December with a Month to Month inflation rate of 6.3%. In 2024 inflation will be the largest in January with a Month to Month inflation rate of 5.9% and experience deflation in October of -5.4%. In 2025, North Sumatra's largest month to month inflation was in December, namely 4.7% and experienced month to month deflation in February of -6%.Abstrak: Tujuan penelitian ini yaitu untuk menentukan model matematis dan tingkat akurasi prediksi tingkat inflasi di Sumatera Utara untuk tahun 2022 menggunakan Maximal Overlap Discrete Wavelet Transform serta mengetahui hasil prediksi tingkat inflasi di Sumatera Utara untuk tahun 2023-2025. Penelitian prediksi inflasi Sumatera Utara ini menerapkan metode Maximal Overlap Discrete Wavelet Transform dengan menggunakan wavelet Haar dalam penyelesaiannya. Hasil yang didapat adalah model prediksi tingkat inflasi Sumatera Utara yaitu dengan nilai interpretasi dari hasil keakuratan MAPE 15% hal ini menunjukkan bahwa jika nilai akurasi 10-20%, dikatakan baik digunakan sehingga penggunaan metode Maximal Overlap Discreate Wavelet Transform dapat digunakan untuk memprediksi tingkat inflasi. Hasil prediksi yang didapat adalah Sumatera Utara mengalami inflasi terbesar pada tahun 2023 di bulan Januari dengan tingkat inflasi Month to Month 24,37% dan inflasi terkecil di tahun 2023 pada bulan Desember tingkat inflasi Month to Month 6,3%. Pada tahun 2024 inflasi terbesar pada bulan Januari dengan tingkat inflasi Month to Month 5,9% serta mengalami deflasi pada bulan Oktober sebesar -5,4%. Pada tahun 2025 Inflasi Month to Month terbesar Sumatera Utara terdapat pada bulan Desember yakni 4,7% dan mengalami deflasi Month to Month pada bulan Februari sebesar -6%.